Development and Application of an Ultrahigh-Temperature Steam Generator. (29th September 2020) - Liu, Song; Wei, Yaping; Chen, Shiqiang; Qin, Liu
Abstract : A device which could produce high-temperature steam quickly was designed. The overall structure of the heating device and the heating pipe of key components were introduced mainly, and the working process of the heating device was analyzed and discussed. This high-temperature steam device with high heating efficiency, produces steam fast and could realize precise temperature control. This device could expand application research of polymer materials and composite materials and provide key guide parameters in the process of technical research.